PENGAPLIKASIAN TURBIN AIR CROSSFLOW PADA ALIRAN SUNGAI DI KIPAS RIVER TUBING 17, DESA DALEMAN, KECAMATAN TULUNG, KABUPATEN KLATEN, JAWA TENGAH - Indah Widiastuti; Danar Susilo Wijayanto; Taufik Wisnu Saputra; Rizki Ikhsan Ramadhan; Agvendo Heksa Mahendra; Rifai Aditya Pratama Putra; Satriya Nugraha; Irba' Rizka Putri; Linda Widyawati; Siti Fadilah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2024)
This Community service program aims to apply a crossflow water turbine in Daleman Village, Tulung Subdistrict, Klaten Regency. This program, conducted by students from the Mechanical Engineering Education Departments of Sebelas Maret University, primarily seeks to harness the renewable energy potential in the area and raise community awareness. The activities included field surveys, system design, turbine installation, and training for villagers on operation and maintenance. The results show that the program increased the community's awareness and understanding of renewable energy and strengthened their capacity to manage and maintain the implemented technology. The collaboration between students, faculty, and the community throughout the program also fostered positive and sustainable relationships. Overall, this community service initiative significantly contributed to achieving energy self-sufficiency and improving the quality of life for the residents of Daleman Village.